PENGARUH BAURAN PEMASARAN TERHADAPKEPUTUSAN MEMBELI TIKET PESAWAT DI TOTAL NUSA INDONESIA TOUR AND TRAVEL YOGYAKARTA - Hesti Duari, I Putu Hardani (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2014)
Marketing mix is once of the important think to increase and develop a unit bisnis. On this conceptual papper attemp the marketing mix can make good effect by the customer decition to buy a domestic ticket. In tourism indutry especially services industry that marketing mix known as 7P. It is include product, place, price, promotion, people, process and physical evident. 7p of the Marketing Mix here took place at PT. Total Nusa Indonesia Tour & Travel Agencies in Yogyakarta headquarters. The total respondents are 100 respondents with quantitative analysis of data. Through the over all uji F is known that the marketing mix significantly influence the decision to buy a plane ticket at PT Total Nusa Indonesia Tour & Travel in Jogjakarta. And the product is the biggest decision to take the decision to buy a plane ticket. This can occur due to variations domestic flight ticket complete product. Than follow by the other marketing mix component. Keywords : Marketing Mix, purchase decisions buying tickets.